2009
DOI: 10.1089/jmf.2008.0140
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pectin, Polyphenols, and Phytosterols, Alone or in Combination, to Lovastatin for Reduction of Serum Lipids in Familial Hypercholesterolemic Swine

Abstract: Greater than 50% of Americans use some form of a dietary supplement, and a diagnosis of coronary artery disease is associated with higher supplement use. The objective of this study was to compare nutritional supplements (pectin, polyphenols, and phytosterols) to lovastatin to reduce serum cholesterol. Familial hypercholesterolemic (FH) swine received the same amount of basal diet (control) in addition to pectin (30 g/day), polyphenols (20 g/day), phytosterols (6 g/day), and all possible combinations in contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Concomitant administration of statins with food may alter their pharmacokinetic and pharmacodynamic profile. It has been reported that consumption of pectin or oat bran soluble fiber together with lovastatin reduces its absorption (Metzger et al, 2009), whereas alcohol intake does not affect the efficacy and safety of fluvastatin treatment (Smit et al, 1995). On the other hand, fluvastatin treatment in rats on high-fat and high-sucrose diet was lethal, suggesting that both altered statin metabolism and elimination increase plasma levels of aspartate aminotransferase and creatine kinase, resulting in skeletal muscle toxicity (Sugatani et al, 2010).…”
Section: Statins and Cancer: Pros And Consmentioning
confidence: 99%
“…Concomitant administration of statins with food may alter their pharmacokinetic and pharmacodynamic profile. It has been reported that consumption of pectin or oat bran soluble fiber together with lovastatin reduces its absorption (Metzger et al, 2009), whereas alcohol intake does not affect the efficacy and safety of fluvastatin treatment (Smit et al, 1995). On the other hand, fluvastatin treatment in rats on high-fat and high-sucrose diet was lethal, suggesting that both altered statin metabolism and elimination increase plasma levels of aspartate aminotransferase and creatine kinase, resulting in skeletal muscle toxicity (Sugatani et al, 2010).…”
Section: Statins and Cancer: Pros And Consmentioning
confidence: 99%
“…In addition to the cholesterollowering diet, several other dietary interventions have been suggested as some nutritional supplements (pectin, polyphenols, phytosterols). Phytosterols seem to represent the most effective supplementation [27][28][29].…”
Section: Dietmentioning
confidence: 99%
“…Phytosterol can also enforce the reduction of LDL cholesterol, while pectin should be added to another supplement to succeed a lower LDL concentration in familial hypercholesterolemia subjects [27]. In a review of 19 randomized controlled trials, it was concluded that phytosterols/stanols incorporated in different food vehicles such as margarine/fat spreads, butter, salad dressings, mayonnaise, chocolate, low-fat yogurt, bakery products, and ground beef significantly reduced LDL cholesterol concentrations between 8 and 15% at a dose of 1.5-3 g/daily [30].…”
Section: Dietmentioning
confidence: 99%
“…This effect on lipids reduces vascular damage and heart disease. [39][40][41] Yapo et al 42 investigated the fiber content in P. edulis juice and found that the total dietary fiber from yellow passion fruit rind was greater than 73% dry matter, of which insoluble dietary fiber accounted for greater than 60% (w/w). The method they used also revealed that nonstarch polysaccharides were the predominant components (approximately 70%, w/w).…”
Section: -36mentioning
confidence: 99%